Perancangan Arsitektur Enterprise Menggunakan Framework TOGAF ADM Pada SMAN 3 Sidoarjo - Valent Aderiandra; Siti Mukaromah; Doddy Ridwandono (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Currently, SMAN 3 Sidoarjo does not have an enterprise architecture and integrated data. To increase the utilization of IT and IS at SMAN 3 Sidoarjo, development through enterprise architecture is needed. The essence of this proposal is to plan an architectural effort as an aid to improving IS and IT at SMAN 3 Sidoarjo in the future. The method used is The Open Group Architecture Framework – Architecture Development Method (TOGAF ADM). The information obtained utilizes qualitative research obtained from observations, document studies and interviews. The continued impact of this research is business architecture, data architecture, application architecture, and technology architecture. The selected design content includes application portfolio catalog, application/organization matrix, logical data diagram and computer network diagram. It is believed that this recommendation can be a reference for improving or developing IS and IT at SMAN 3 Sidoarjo to realize the vision and mission of SMAN 3 Sidoarjo through business architecture, information systems architecture and technology architecture..